History and Background of Quality Measurement - Chun, Jonathan; Bafford, Andrea Chao (Clinics in Colon and Rectal Surgery, 2014)
Health care quality measurement has become increasingly emphasized, as providers and administrators respond to public and government demands for improved patient care. This article will review the evolution of surgical quality measurement and improvement from its infancy in the 1850s to the vast efforts being undertaken today.
Keywords: surgical quality; quality improvement; quality measures; history